Pengaruh Gaya Kognitif Terhadap Hasil Belajar Kimia pada Materi Redoks dengan Menggunakan Model Contextual Teaching and Learning - Sekarrini, Olgarinda; Hadinugrahaningsih, Tritiyatma; Muhab, Sukro (Jurnal Riset Pendidikan Kimia (JRPK), 2021)
This study aims to compare the chemistry learning outcomes in redox between students who have the cognitive style of the Field Dependent and Field Independent on the Contextual Teaching and Learning model. This research was performes in X MIA class, SMA 36 Jakarta. The research method used is quantitative with comparative techniques. Sampling in this study used a purposive sampling technique. Learning used in two classes is the Contextual Teaching and Learning model. The instruments used are in the form of Group Embedded Figure Test (GEFT) and posttest. The data obtained are then analyzed using the t-test. The average learning outcomes obtained by students with the Field Independent cognitive style were 80.77 and in students with the Field Dependent cognitive style was 54.58. The results showed differences in student learning outcomes between students with Independent Field cognitive style and students with Field Dependent cognitive style (tcount = 10.62; ttable = 1.68, tcount> ttable). So that it can be concluded that the cognitive style can have a positive effect on student learning outcomes at redox with the Contextual Teaching and Learning model. Keywords: Cognitive Style, Learning Outcomes, Redox